Boko Haram Insurgency and National Security Challenges in Nigeria: An Analysis of a Failed State (Global Journal of Human-Social Science, 2014)
This paper examined the activities of the Boko Haram sect and how it has impeded the economic, political and social matrix of the Nigerian polity. The paper argued that the insurgence of the sect would continually be a national security challenge in-spite of the marginal lip-service of the government to curb the heinous activity. The paper relied more on secondary data-journals, magazines newspapers internet and the theoretical framework is Durkheim and Merton Anomie theory etc . The paper concluded that development cannot take place in an atmosphere of insecurity the symptoms of a failed state are made manifest on a daily basis in Nigeria such as poor governance, destruction of lives and properties, population displacement, lack of basic amenities. Hence, the Nigerian government has failed in its social responsibility to secure lives and properties of the populace. It recommends for collective and holistic machinery, not only by the Nigerian state, but also by the entire African nations and United States to curb not only Boko Haram insurgencies, but also any pockets of militia activity threatening the existence of the state. Also, the deployment of neighborhood watch (NW) would be a complimentary effort to the machinery of government to identify and locate the sect for such a time as this.
Keywords: boko haram; insurgents; security; sectarians; development; neighborhood watch